If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 8 + -8 = -3 + 2n Reorder the terms: 8 + -8 + 3n = -3 + 2n Combine like terms: 8 + -8 = 0 0 + 3n = -3 + 2n 3n = -3 + 2n Solving 3n = -3 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 3n + -2n = -3 + 2n + -2n Combine like terms: 3n + -2n = 1n 1n = -3 + 2n + -2n Combine like terms: 2n + -2n = 0 1n = -3 + 0 1n = -3 Divide each side by '1'. n = -3 Simplifying n = -3
| x^2+47x=48 | | (x-3)=6x+17 | | 9.4=5.6-d | | 0.3(6x-9)=-27 | | Tv=2v-20 | | 31+12x-32-10x=27+29 | | v=hpir^2 | | 65+y=72 | | -7(m+3)=2(12-6m) | | .15x+.05(2-x)=.10(17) | | 150s(225s-3.50)=2000 | | -2+3x=-5 | | 0=25a+2 | | 4a-5b=6b | | (2x-9)+(3x^2-5x+3)=x | | 9x+29-x-28=87 | | -1+5x=39 | | (6n-4)+14=1 | | .24(10000)-.02y=.08(y+10000) | | -15-15x=-4x-8x | | 5x-15=25y | | 2(X+4)+2=4 | | -(3x-1)= | | 2(2x-2)=-16 | | 9-2(x-3)=9 | | 5x+5(3x-7)=125 | | .30(24)+.05x=.15(12+x) | | 2d^2=8-10d | | |x+1|=0 | | X=4.5+y | | 174=22x+8+6x-2 | | (3x^2+2x-6)+(x^2-4x)=x |